Psychosocial Support for Teachers Experiencing Emotional Challenges in Special Schools: Implications for Counseling - Olatunbosun, Stella Oluwakemi; Pillay, Jace (CV Sinergi Ilmu dan Publikasi, 2026)
This study examined psychosocial support mechanisms for special education teachers (SETs) in Southwest Nigeria, with a focus on special primary schools by emphasizing implications for counseling and psychological strategies amid emotional challenges. A quantitative design was utilized by targeting SETs. Data were collected through the Psychosocial Support for Teachers Questionnaire (PSSTQ; α=0.82) and analyzed using descriptive statistics such as frequencies, percentages, and percentile ranks. Findings revealed high stress among SETs, propelled by scarce resources such as inadequate teaching materials, outdated technology, and emotional strain from bonding with students facing significant challenges. Notable gaps include insufficient professional development and social support networks, which are hindering stress management and optimal performance. In conclusion, the study emphasizes the need for an elaborate approach to support SETs, integrating professional development, psychological counseling, and the creation of robust support networks. It advocates for policy interventions to bolster resources and support systems, highlighting the indispensable role of SETs in fostering the growth and development of learners with special needs. The implications for counseling include the recommendation for targeted support strategies that address the unique challenges SETs face, promoting their well-being and, by extension, enhancing the quality of education for learners in special schools.